Social Movements, Social Problems and Social Change - Yadav, Ajay Kumar (Academic Voices: A Multidisciplinary Journal, 2016)
Social movement is an organized effort by a significant number of people to change (or resist change in) some major aspect or aspects of society. Sociologists have usually been concerned to study the origins of such movements, their sources of recruitment, organizational dynamics, and their impact upon society. Social movements must be distinguished from collective behavior. Social movements are purposeful and organized; collective behavior is random and chaotic. Social movements include those supporting civil rights, gay rights, trade unionism, environmentalism, and feminism. Collective behaviors include riots, fads and crazes, panics, cultic religions, rumors. This paper deals with formation of social movement, emergence of social movement, social problems and social change. Academic Voices Vol.5 2015: 1-4